Development and Characterization of Chitosan Nanoparticles Loaded with Amoxicillin as Advanced Drug Delivery Systems against Streptococcus Mutans - J Jasem , Abdullah; Maha A Mahmood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study’s primary objective was to create nanotechnology-based, precisely regulated drug delivery devices. Antibiotic Amoxicillin was chosen, and chitosan nanoparticles (CSNPs) were chosen to transport the medicine. Using the ionic gelation process, chitosan solution NPs were synthesized using tripolyphosphate (TPP). Antibiotic-loaded chitosan nanoparticles (CSNPs) were then used to create a nanocomposite with good performance. The resultant nanocomposite can be put to use as an effective, non-toxic antimicrobial agent. CMCS has a considerably wider range of uses as an anti-bacterial agent than chitosan since it is soluble in a wide pH range. Due to its water solubility, Ten S. mutans isolates were purified in two mediums, making it easy to use and elicit a variety of biological activities of CMCS in pharma and cosmetics. Tryptone yeast extract cysteine sucrose mitis salivarius bacitracin agar. MS colonies on MSBA plates were blue, spherical or ovoid, 1-2 mm in diameter, with elevated surfaces that stuck well to the agar. Rough colonies had a rough or frosted glass surface. Samples treated with chitosan, carboxymethyl chitosan, chitosan nanoparticles, and their nanocomposite containing antibiotics (Amoxicillin) stymied the growth of Streptococcus mutans. Chitosan nanoparticles and their loaded antibiotics were discovered by scanning Electron Microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). In addition, the cytotoxicity of both the nanocomposite and amoxicillin loaded on nano-chitosan were compared to that of amoxicillin alone. PH 4.5 with a drug/polymer ratio of 1:2 (w/v) resulted in 89.33% entrapment and 53% loading efficiency for Amoxicillin in terms of their particle size, surface charge, bond interaction, and shape, respectively. A zeta potential of +24.5 mV and an average particle size of 258 nm were found through analysis. The results showed the superior antibacterial efficacy of the AMX-CSNPs. It can be concluded that AMX-CSNPs and CSNPs displayed acceptable physicochemical characterizations, and effective antimicrobial activities against Streptococcus mutans. These formulations could enhance drug delivery for treating cariogenic bacteria causing dental caries.